2015
DOI: 10.1556/032.65.2015.s2.27
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Tourist Flow from the US to Taiwan

Abstract: It is important for Taiwanese policy makers to understand how economic factors affect US tourists' decision to travel to Taiwan. For the long-run analysis, Johansen's cointegration test reveals that three cointegration vectors exist among the model variables, indicating a long-run relationship. To conduct a short-run analysis, this paper employs vector auto regression (VAR) to estimate the responses of US tourists in Taiwan to the shocks of changes to personal disposable income, cost of living, and substitute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In addition to its own price, Chen and Kang (2015), Kim and Song (1998), Song et al. (2000) and Song and Witt (2003, 2006) showed that substitute prices are important in competitive problems.…”
Section: The Model and Data Setmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to its own price, Chen and Kang (2015), Kim and Song (1998), Song et al. (2000) and Song and Witt (2003, 2006) showed that substitute prices are important in competitive problems.…”
Section: The Model and Data Setmentioning
confidence: 99%
“…The non-economic dummy variable is set to capture the influence of the one-off SARS event. (Chen and Kang, 2015).…”
Section: The Model and Data Setmentioning
confidence: 99%
See 1 more Smart Citation
“…The tourist services market is a very variable and diffi cult to predict market (Chen & Kang, 2015) that reacts quickly to factors and turmoil occurring in the international, national and local environment. Impact of these factors is evident both on the supply and on the demand side (Zdon-Korzeniowska & Rachwał, 2011).…”
Section: Introductionmentioning
confidence: 99%